IMPLEMENTASI PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI PENDIDIKAN DASAR - Pratama, Angga; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the implementation of the Islamic Religious Education curriculum at State Elementary School 3 Wayhalim, Bandar Lampung, and to identify the factors influencing its success in meeting students' needs in the modern era. The research employs a descriptive qualitative method, with data collected through observations, in-depth interviews, and document analysis. Findings reveal five main factors affecting the implementation of the PAI curriculum: time constraints, teacher competence, community involvement, facility support, and curriculum flexibility. Observations show that lecture methods dominate instructional time, which tends to reduce the effectiveness of interactive learning in fostering students' emotional intelligence and understanding of religious values. Additionally, community involvement and limited facilities, especially in providing technology that supports inclusive learning, pose significant challenges. The results of this study show the importance of teacher training in using interactive teaching methods and digital technology, as well as improving facilities to support student needs. It further recommends stronger collaboration between schools and the community in curriculum design and evaluation to enhance the relevance of religious values in students' daily lives. With these supports, the PAI curriculum is expected to be implemented more effectively and adaptively, playing an optimal role in shaping students' character with integrity and tolerance.